Analisis Penjualan Alat-Alat Olahraga Dikota Pontianak - Elsye Olivia Barahen Putri; Uray Gustian; Rubiyatno Rubiyatno (Journal on Education, 2024)
The sports industry is a process of processing goods and services into finished goods and semi-finished good with the aim of making a profit to seek as much profit as possible with added value in the process of providing sports equipment. Various brands of sports products are sold in 21 existing sports shops. In the city of Pontianak such as adidas,asic,mizuno,speed,and others. The aim of this research is to find out what sports equipment,sports products and sports brands are most in demand bye the people of Pontianak city. There were 21 sports shops studied in the city of Pontianak,west Kalimantan. The research instrument used a closed questionnaire with a total of 6 questions. The data from the research shows that the sports equipment that is most popular is badminton rackets with a tota of 21,volleyball 17,football 17,futsal ballas 16 sold. The sports products most popular with the people of Pontianak city are football shoes with a total of 18,17 futsal shoes,15 football shirts+pants,14 volley ball shirts+pants sold. While the most popular brand of goods was lining with 19,mizuno 17,and yonex 17 sold.